III International Guidance Congress: A Learning Space for Students in Training (Costa Rican Journal of Guidance & Counseling, 2025)
Objective: To recognize the contributions of the Third International Guidance Congress to the training of students in the Guidance program at the University of Costa Rica.Methodology: The research was conducted using a qualitative methodology with a phenomenological approach, with the participation of 14 students who attended the Guidance Congress, which was held in October 2024. Questionnaires and discussion circles were used, and the conference was recorded and transcribed into a database for analysis.Results: The results are organized into expectations and significant learning categories. It is noteworthy that the expectations of participating students to complement their university education were met, and it provided a space for exchange. In addition, significant learning was identified in terms of the importance of professional updating, the incorporation of technology into guidance activities, and understanding different work contexts and intervention methodologies.Conclusions: This conference is an opportunity for personal and professional development, and it is essential, from the initial university education, to contribute to the promotion of the commitment to professional updating.
Keywords: Congress, Guidance, Updating